Forecasting the discharge into Hoa Binh reservoir by applying the connecting model marine - imech1D - Cuong, Nguyen Tien; Phuong, Trinh Thu (Vietnam Journal of Mechanics, 2008)
Da river is the biggest one of three rivers: Da, Thao and Lo which flow into Hong river, so calculating and forecasting correctly the discharge to Hoa Binh reservoir take an important role in managing the task of flood preventing in the Hong - Thai Binh river system. In this paper, a connected hydraulic-hydrological model is developed. The model was applied to forecast the discharge into Hoa Binh reservoir in the flood season 2006. The difference of this connected hydraulic-hydrological model in comparison with the other hydrological models is using the complete Saint-Venant 1D to simulate flow in rivers. Results of verification of the model show that it is good enough for practice